Threat or treat: Exposure assessment and risk characterisation of chemical contaminants in soft drinks and chocolate bars in various Polish population age groups - Lorenzo Marincich; Michele Protti; Roberto Mandrioli; Laura Mercolini; Łukasz Woźniak (EFSA Journal, 2023)
Abstract In the frame of the European Food Risk Assessment (EU‐FORA) fellowship programme, two studies on chemical contaminants in food matrices were carried out in Warsaw, Poland, at the Department of Food Safety and Chemical Analysis, Institute of Agricultural and Food Biotechnology. The first study addressed health concerns about the dietary exposure to bisphenol A (BPA) contamination due to consumption of soft drink by Polish population. BPA is an organic additive used in the production of epoxy resins and polycarbonate plastics and because of this it is used in the internal coating of cans and in plastic bottle production. Depending on several factors, BPA can migrate from these materials to the soft drink and so, it can be ingested by consumers causing hormonal and reproductive disorders. To estimate the Polish population exposure to BPA, several soft drinks belonging to different brands were purchased from a supermarket in the city of Warsaw and analysed. The result of the analysis highlight that mean BPA exposure in the Polish population exceeds the tolerable daily intake proposed by the EFSA scientific opinion, raising health concerns. On the other hand, the second study, focused on cadmium exposure due to chocolate consumption by Polish population, did not raise any health concern. Cadmium is a heavy metal that naturally occurs in its inorganic form in the environment and its presence in chocolate derives only from the cocoa beans and not from contamination during processing. Its accumulation in the human body can create several adverse effects, including renal dysfunction and failure. To estimate the Polish population exposure to cadmium, several chocolate bars were purchased from a supermarket in the city of Warsaw and analysed. The results of the analysis show that cadmium exposure in the Polish population does not exceed the tolerable weekly intake proposed by the EFSA scientific opinion.